2015
DOI: 10.1002/cyto.a.22794
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput linear optical stretcher for mechanical characterization of blood cells

Abstract: This study describes a linear optical stretcher as a high-throughput mechanical property cytometer. Custom, inexpensive, and scalable optics image a linear diode bar source into a microfluidic channel, where cells are hydrodynamically focused into the optical stretcher. Upon entering the stretching region, antipodal optical forces generated by the refraction of tightly focused laser light at the cell membrane deform each cell in flow. Each cell relaxes as it flows out of the trap and is compared to the stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…It remains to be shown that such a force balance mechanism exists in suspended cells. The resistance of cells against deformations has been investigated via techniques such as magnetic twisting cytometry (MTC) [12,13], atomic force microscopy (AFM) [14,15], laser tracking microrheology [13], hydrodynamic stretching with flow-cytometers [16][17][18][19][20], and optical stretcher (OS) [1,[21][22][23][24]. These studies were performed on various cell types [7,25] and often indicate that actin filaments are a major contributor to the mechanical properties of cells.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be shown that such a force balance mechanism exists in suspended cells. The resistance of cells against deformations has been investigated via techniques such as magnetic twisting cytometry (MTC) [12,13], atomic force microscopy (AFM) [14,15], laser tracking microrheology [13], hydrodynamic stretching with flow-cytometers [16][17][18][19][20], and optical stretcher (OS) [1,[21][22][23][24]. These studies were performed on various cell types [7,25] and often indicate that actin filaments are a major contributor to the mechanical properties of cells.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 This technique could not only significantly deform cells, but could also induce cell damage upon exerting an estimated fluidic force on the cells exceeding 1 nN. 28 Other implementations are to deform the cells when they flow through at a high speed in narrow microfluidic channels, with cross-sectional dimensions close to or smaller than the cell size. [29][30][31][32] Specifically, in the real-time deformability cytometry (RT-DC) technique, the characterization throughput reaches 10 2 -10 3 cells per s. 30 However, the extracted cell stiffness in the RT-DC technique is only valid for cell deformations over a short time scale of ∼1 ms, 33 which is not comparable (around an order of magnitude higher) with the static cell stiffness measured using the conventional static testing.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed for investigating the difference of the mechanical properties of healthy and sick RBCs. For example, parachute and slipper shapes are produced, respectively, in small and large one-dimensional microchannels (22), while opticallyinduced deformation using the optical stretcher is typically limited to cell elongation along a defined direction due to the applied antipodal stretching forces (19,23). For example, parachute and slipper shapes are produced, respectively, in small and large one-dimensional microchannels (22), while opticallyinduced deformation using the optical stretcher is typically limited to cell elongation along a defined direction due to the applied antipodal stretching forces (19,23).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed for investigating the difference of the mechanical properties of healthy and sick RBCs. Common techniques for addressing this purpose are based on particular microfluidic channels (10)(11)(12)(13), and on various electrical/optical techniques, such as atomic force microscopy (4,14), dielectrophoresis (15), and optical trapping techniques (16)(17)(18)(19)(20)(21). For example, parachute and slipper shapes are produced, respectively, in small and large one-dimensional microchannels (22), while opticallyinduced deformation using the optical stretcher is typically limited to cell elongation along a defined direction due to the applied antipodal stretching forces (19,23).…”
Section: Introductionmentioning
confidence: 99%